Seven-up, the Drosophila homolog of the COUP-TF orphan receptors, controls cell proliferation in the insect kidney. - Kerber, B.; Fellert, S.; Hoch, M. (Genes & Development, 1998)
Morphogenesis of the insect kidney, the Malpighian tubules, is controlled in Drosophila by a single large cell, the tip cell. It has been postulated that this cell sends out a mitogenic signal that induces the division of neighboring cells. The signal and the molecules that receive it have remained elusive. We show that the COUP-TF-related nuclear orphan receptor Seven-up is a key component that becomes induced in response to mitogenic EGF receptor signaling activity emanating from the tip cell. Seven-up in turn is capable of regulating the transcription of cell cycle regulators.